2c+9-2c=6

Simple and best practice solution for 2c+9-2c=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2c+9-2c=6 equation:


Simplifying
2c + 9 + -2c = 6

Reorder the terms:
9 + 2c + -2c = 6

Combine like terms: 2c + -2c = 0
9 + 0 = 6
9 = 6

Solving
9 = 6

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 6y*1-4y=-24 | | 1-2cosx=1 | | 6x-19x+10=0 | | 9a+3(9-7)= | | y=4x+9.5 | | 0.5x^2-75x+937.5=0 | | .5(x+7)=x-4 | | 4/7x-18=x | | 3-4x=x+7 | | 8-3x/5=2x/3-14/3 | | 1/3x=x-14 | | 40x+20y=5600 | | -5(p+2)=6-p | | 2(6w-5)=3(4w-1)-8 | | 9t=4(2t-5) | | 9-2(x-7)=7(x-7) | | 2-5(x+1)=5-3x | | 5(x+1)2+2=22 | | 2(8x-3)=20x-58 | | y=67x-7 | | 2(3x+1)=6-3x | | .50x+5=1x | | 7-3(4-x)=-26 | | 5-2(x+1)=17 | | -2(x+1)=5 | | 3(4y-4)-y=11 | | 6x-12x-5=0 | | 1/9x-5/3=0 | | 12(1/4)-8(3/10) | | 12x-4=3(x+1)-x | | 6x-4y=-20 | | 7÷2(1/5) |

Equations solver categories